2022
DOI: 10.1182/blood.2022017575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine starvation impairs acute myeloid leukemia progression

Abstract: Targeting altered tumor cell metabolism might provide an attractive opportunity for patients with acute myeloid leukemia (AML). An amino acid dropout screen on primary leukemic stem cells and progenitor populations revealed a number of amino acid dependencies, of which methionine was one of the strongest. By using various metabolite rescue experiments, NMR-based metabolite quantifications and 13C-tracing, polysomal profiling, and ChIP-seq, we identified that methionine is used predominantly for protein transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…There was a significant decrease in hemoglobin in the methionine-restricted group in both females and males, with a small but significant decrease in red blood cells in females. To our knowledge, hemoglobin values have not been previously reported in methionine restriction but are in line with data reported for complete methionine starvation in acute myeloid leukemia (28). We then performed immunohistochemistry on the tumor tissue.…”
Section: Dietary Methionine Restriction Increases Pd-l1 Expression An...supporting
confidence: 84%
“…There was a significant decrease in hemoglobin in the methionine-restricted group in both females and males, with a small but significant decrease in red blood cells in females. To our knowledge, hemoglobin values have not been previously reported in methionine restriction but are in line with data reported for complete methionine starvation in acute myeloid leukemia (28). We then performed immunohistochemistry on the tumor tissue.…”
Section: Dietary Methionine Restriction Increases Pd-l1 Expression An...supporting
confidence: 84%
“…Many studies such as this have identified high‐fat diet to worsen leukemia progression, 3 but none have implemented a low‐fat diet as a possible intervention to improve treatment. One study identified AML cells to be high in amino acids such as methionine, cysteine, and lysine, and showed that depleted methionine from the diet in vivo slowed leukemic progression 26 . However amino acid depletion diets are difficult to implement in clinical settings, as this requires a very specific diet formulation and strict adherence.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified AML cells to be high in amino acids such as methionine, cysteine, and lysine, and showed that depleted methionine from the diet in vivo slowed leukemic progression. 26 However amino acid depletion diets are difficult to implement in clinical settings, as this requires a very specific diet formulation and strict adherence.…”
Section: Discussionmentioning
confidence: 99%
“…SAM is synthesised by methionine adenosyltransferase (MAT) from methionine in the one‐carbon metabolism pathway. Methionine depletion reduces SET‐domain containing 2 (SETD2)‐catalysed H3K36me3, which is accompanied by decreased transcription, enhanced apoptosis, and cell cycle arrest (Cunningham et al ., 2022). Methionine deficiency also leads to reduced SAM levels and specific declines in H3K4 methylation in yeast, Caenorhabditis elegans and human cells (Sadhu et al ., 2013; Ding et al ., 2015).…”
Section: Metabolites and Epigenetic Modificationsmentioning
confidence: 99%